Assessment of video-based e-learning in a construction measurement course. Issue 1 (2nd January 2022) - Wong, Johnny K. W.; Oladinrin, Olugbenga T.; Ho, Christabel M. F.; Guilbert, Eric; Kam, Roy
ABSTRACT: E-learning has been touted as a new phenomenon and formidable frontier of education, offering tremendous benefits to teachers, learners and educational administrators. However, despite the adoption of e-learning in many educational institutions worldwide, to enhancing teaching and learning experience, delivery of construction measurement courses has been limited to traditional lecture approach and the use of little technology such as PowerPoint. Therefore, this study investigates learners' satisfaction, benefits, and the usefulness of e-learning approach, relative to instructional videos. A total of 76 undergraduate construction students were surveyed using a closed and open-ended questionnaire in one of the universities in Hong Kong. The results showed that students were satisfied with design and content of the instruction videos. Students also considered e-learning approach useful because it allows them to control their pace, time and location for learning. Learners prefer blended learning, i.e. a combination of e-learning (at 41%) and traditional face-to-face method (at 59%). The participants opined that blended learning has more significant benefits in delivering measurement course. The results of this study should assist educators in structuring blended learning approach.